Afro-American Student Union [fundraising booth] (1988)
Three Black students are behind the booth, and two of them are clapping and possibly singing. The third person, wearing a sweater with 'Los Angeles' printed on it, is smiling and laughing with the others. The back of the photograph reads: 'Poly Royal 88: Robert Tell, Stacy G., Mo P., Tni, Tisha, Angie Lee, Vanessa.'